Wellness Center Di Kota Denpasar Dengan Pendekatan Healing Environment - I Gede Haryanta Darmawan; I Wayan Wirya Sastrawan; I Nyoman Warnata (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Wellness Center is related to activities that are healthy for the body and soul. Activities in the form of a place to exercise, meditation, consultation on health problems and others, where in addition to being healthy for the body, it also teaches a healthy lifestyle and is kept away from disease. With a healing environment approach such as the senses, nature, psychology, it is hoped that it will create a Wellness Center that blends with the circumstances and natural cycles. The healing environment approach is the basis for the development of the Wellness Center design, which is the answer to overcoming human behavior with nature. Located in the city of Denpasar, it will make it easier for people to exercise with a natural atmosphere and complete facilities.